Detection of PrPres in Genetically Susceptible Fetuses from Sheep with Natural Scrapie - Garza, María Carmen (Public Library of Science, 2011)
Scrapie is a transmissible spongiform encephalopathy with a wide PrPres dissemination in many non-neural tissues and with high levels of transmissibility within susceptible populations. Mechanisms of transmission are incompletely understood. It is generally assumed that it is horizontally transmitted by direct contact between animals or indirectly through the environment, where scrapie can remain infectious for years. In contrast, in utero vertical transmission has never been demonstrated and has rarely been studied. Recently, the use of the protein misfolding cyclic amplification technique (PMCA) has allowed prion detection in various tissues and excretions in which PrPres levels have been undetectable by traditional assays. The main goal of this study was to detect PrPres in fetal tissues and the amniotic fluid from natural scrapie infected ewes using the PMCA technique. Six fetuses from three infected pregnant ewes in an advanced clinical stage of the disease were included in the study. From each fetus, amniotic fluid, brain, spleen, ileo-cecal valve and retropharyngeal lymph node samples were collected and analyzed using Western blotting and PMCA. Although all samples were negative using Western blotting, PrPres was detected after in vitro amplification. Our results represent the first time the biochemical detection of prions in fetal tissues, suggesting that the in utero transmission of scrapie in natural infected sheep might be possible.